Evaluation of phenolic-linked bioactives of camu-camu (Myrciaria dubia Mc. Vaugh) for antihyperglycemia, antihypertension, antimicrobial properties and cellular rejuvenation. (November 2015) - Fujita, Alice; Sarkar, Dipayan; Wu, Shibiao; Kennelly, Edward; Shetty, Kalidas; Genovese, Maria Inés
Abstract: Camu-camu ( Myrciaria dubia (Kunth) Mc. Vaugh (Myrtaceae)) has shown potential for food and human health applications due to its rich bioactive functional properties linked to high antioxidant activity. The main objective of this study was to identify antioxidant-linked bioactive phenolic profiles in spray-dried and freeze dried camu-camu pulp and to evaluate potential functionality associated with anti-hyperglycemia and anti-hypertension properties using in vitro enzyme assay models. Further, antimicrobial properties and planarian-based cellular protection and regeneration were also investigated. Phenolic compounds, such as ellagitannins, ellagic acid, quercetin glycosides, syringic acid and myricetin were detected in camu-camu by LC–TOF-MS. Freeze dried camu-camu powder showed superior phenolic-linked antimicrobial properties and higher hyperglycemia relevant enzyme inhibitory activity compared to the spray dried samples. Besides that, freeze-dried powders and spray-dried (6% gum arabic at 120 °C) powders were more effective against prokaryotic Staphylococcus aureus and showed higher inhibition than ampicillin. Cellular regeneration of eukaryotic planarian model was stimulated with camu-camu powders when compared to control and showed potential of camu camu for redox-linked cellular protection and rejuvenation. Overall camu-camu rich in phenolic bioactive profiles showed superior antidiabetic and antimicrobial properties and has potential as part of dietary strategies in the management of early stages of type 2 diabetes and associated complications. Highlights: Camu-camu powders, their bioactives and functionality Bioactives showed potential for redox-linked protection of eukaryotic cells. Camu-camu has potential for the management of early stage type 2 diabetes. Ellagitannins, ellagic acid, quercetin and myricetin were detected in camu-camu.